McGraw-Hill dictionary of mathematics (McGraw-Hill, 1997)
Mathematicians, scientists, engineers, and students can turn to this dictionary for definitive coverage of all branches of mathematics, both pure and applied. Featuring 3,600 terms, the book defines terms and expressions in algebra, number theory, operator theory, logic, complex numbers, finite mathematics, topology, and other areas--each with definition identified by the field in which it is primarily used. Included are numerous cross references and an appendix with tables of integrals and derivatives.